2016
DOI: 10.1369/0022155416649579
|View full text |Cite
|
Sign up to set email alerts
|

A Buffered Alcohol-Based Fixative for Histomorphologic and Molecular Applications

Abstract: Formalin-fixed paraffin-embedded (FFPE) tissue is the predominant preparation for diagnostic histopathological evaluation and increasingly the biospecimen on which molecular diagnostics are performed. However, formalin is carcinogenic and results in cross-linking of proteins and nicking and alterations of nucleic acids. Alternative fixatives, including 70% ethanol, improved biomolecular integrity; however, they have yet to replace neutral-buffered formalin (NBF). Herein, we describe the phosphate-buffered etha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 72 publications
4
48
0
1
Order By: Relevance
“…This is not the case for the "gold standard" NBF, as emphasized in the work of Chung et al, (2018) in which scientists reported a progressive decrease of H&E staining intensity following 1 week to 6 months fixation. Finally, we observed some artifactual changes that have been previously described in alcohol-based fixed tissues, in particular shrinkage and hardening effects independently by fixation times (Perry et al, 2016). However, the degree of these alterations did not significantly influence the establishment of a proper diagnosis in our samples.…”
Section: Discussionsupporting
confidence: 58%
“…This is not the case for the "gold standard" NBF, as emphasized in the work of Chung et al, (2018) in which scientists reported a progressive decrease of H&E staining intensity following 1 week to 6 months fixation. Finally, we observed some artifactual changes that have been previously described in alcohol-based fixed tissues, in particular shrinkage and hardening effects independently by fixation times (Perry et al, 2016). However, the degree of these alterations did not significantly influence the establishment of a proper diagnosis in our samples.…”
Section: Discussionsupporting
confidence: 58%
“…An alternative fixative showed the highest PERM values (mean = 121.23), while neutral buffered formalin showed the lowest PERM values (mean = 32.02) among tested fixatives (11). RNA isolated from tissue fixed in the alternative fixative resulted in a mean C q value of 34.46 for HPRT , whereas the C q value was higher in samples generated from formalin-fixed tissues (mean C q = 41.27).…”
Section: Resultsmentioning
confidence: 94%
“…In a retrospective study, PERM values were also correlated with RT-qPCR data (11). An alternative fixative showed the highest PERM values (mean = 121.23), while neutral buffered formalin showed the lowest PERM values (mean = 32.02) among tested fixatives (11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The key step of histological analysis of a tissue needs a proper fixation method and consequently availability of appropriate fixatives for that purpose. A proper fixative fluid should fulfill the following criteria: 1) prevention of autolysis, 2) preservation of structures between and 3) within the cells and inhibition of contamination by bacterial or molds growth (Perry et al, 2016). Therefore, comparison of various fixative solutions for blastema tissue in order to choose the proper one for the desired purpose would offer valuable information to utilize in histological evaluation in regeneration studies.…”
Section: Introductionmentioning
confidence: 99%